IMPLEMENTING PROJECT-BASED LEARNING FOR EFL STUDENTS’ WRITING ACHIEVEMENT AT TERTIARY LEVEL - Ilham, Ilham (University of Kuningan, 2022)
Writing is the process of recursively producing written work. This study aims to explore the effectiveness of project-based learning to elevate the students’ academic writing at the tertiary level and to know the students’ opinion of the implementation of project-based learning in teaching writing. A mixed method design is employed and it is conducted in twelve sessions. It involves thirty- eight students of the English Department of a private university in Mataram West Lombok, Indonesia who attend academic writing class in the academic year 2022-2023. Project-based learning through the Canva application is conducted in academic writing class. To collect the data, writing tests and interviews were used. The finding revealed that project-based learning is able to improve the students writing achievements, the students perceived project-based as interesting, challenging, motivating, enhancing their English, and increasing their creativity. Project-based enabled them to work together in groups and to think contextually about the problem given. To conclude, it is advisable for EFL teachers to implement project-based learning integrating ICT.